A COMPARATIVE STUDY OF FEMININE LITERARY EXPRESSION IN ENGLISH AND UZBEK FICTION AND THEIR TRANSLATIONS - Xolboyeva Marjona Rahmon qizi (Modern American Journals, 2025)
This article presents a comparative study of feminine literary expression in English and Uzbek fiction, with a particular focus on how such expressions are preserved or transformed in translation. By analyzing stylistic and cultural elements, it highlights the differences in portraying female characters and voices in both traditions. The study also discusses the role of translators in maintaining authenticity and gender nuances, using examples from classical and modern literature, including the translation of “Oʻtkan Kunlar” by Abdulla Qodiriy.
Keywords: feminine expression, literary translation, English fiction, Uzbek fiction, gender in literature, translation strategies, cultural semantics.